Optimum Time for Contestants For The Swinging Flashlight Test: A Quantitative Study - Edworthy, A Gene; Williams, T David (Canadian Journal of Optometry, 1983)
The swinging flashlight test has been used for years in optometric practice to determine the integrity of the afferent visual pathways. This paper is an attempt to quantify the duration of the stimulus directed into the eye and the rate at which the stimulus should be alternated between the eyes.